Major Current Environmental Problems in Bangladesh: Causes, Implications, and Citizen Solutions - Ahmed, Rashed (AMPLITUDO : Journal of Science and Technology Innovation, 2025)
Bangladesh faces significant environmental challenges stemming from rapid industrialization, urbanization, and climate change impacts. This article examines the major environmental problems plaguing the nation, focusing on their causes, implications, and potential citizen-driven solutions. Key issues include air and water pollution exacerbated by industrial emissions and inadequate waste management systems. Rapid deforestation, driven by urban expansion and agricultural practices, threatens biodiversity and exacerbates soil erosion. The implications of these environmental problems are profound, affecting public health, food security, and socioeconomic stability. Vulnerable populations, particularly in low-lying coastal areas, face increased risks from climate-induced disasters like cyclones and flooding. Moreover, contamination of water sources with pollutants poses severe health risks, contributing to the prevalence of waterborne diseases. Addressing these challenges requires collaborative efforts involving government policies, private sector initiatives, and active citizen participation. Promoting sustainable practices, such as renewable energy adoption and efficient waste management, can mitigate environmental degradation. Additionally, empowering communities through education and awareness campaigns enhances resilience and fosters grassroots solutions. By analyzing the causes, understanding their implications, and exploring citizen-led interventions, this article provides a comprehensive overview of Bangladesh's environmental landscape and underscores the urgency of proactive measures to achieve sustainable development.